ȻENTOL TŦE TEṈEW̱ (together with the land) Part 2: Indigenous Frontline Practice as Resurgence - de Finney, Sandrina; Wright Cardinal, Sarah; Mowatt, Morgan; Claxton, Nick XEMŦOLTW̱; Alphonse, Danielle; Underwood, Tracy; Kelly, Leanne; Andrew, Keenan (International Journal of Child, Youth and Family Studies, 2020)
In this paper, Part 2 of a two-paper series, we extend our learning on land- and water-based pedagogies from Part 1 to outline broader debates about upholding resurgence in frontline practice with Indigenous children, youth, and families. This article shares key learning from an Indigenous land- and water-based institute held from 2019 to 2020 that was facilitated by knowledge keepers from local First Nations and coordinated by faculty mentors from the School of Child and Youth Care at the University of Victoria. The purpose of the one-year institute was to convene a circle of Indigenous graduate students and faculty to engage in land- and water-based learning and meaningful mentoring connections with Indigenous Old Ones, Elders, and knowledge keepers. Students participated in land- and water-based activities and ceremonies, learning circles, and writing workshops, and were invited to develop and share culturally grounded frameworks to inform their frontline practice with children, youth, families, and communities. Drawing on a storytelling approach to share our learning from this institute, we explore the praxis and challenges of resurgence in deeply damaging colonial contexts. Our individual and collective reflections on Indigenous land-based pedagogies focus on local knowledges, our own diverse perspectives and frontline work, and ethical land and community engagements as integral to resurgent Indigenous practice.